Are doctors better health ministers? - Adam Pilny; Felix Rösel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Appointing or electing professionals to be public officials is a double-edged sword. Experts can use their rich knowledge to implement reforms, but they can also favor their own profession. In this study, we compare physician-trained state health ministers to ministers of other professions in Germany during 1955-2017. German state health ministers have great power to determine hospital capacities and infrastructure. Our results show that physiciantrained health ministers increase hospital capacities, capital, and funding by the statutory health insurance (SHI). This prompts hospitals to hire more physicians, but with little impact on hospital outputs. As a result, total factor productivity (TFP) growth in hospital care slows down substantially under physician-ministers. At the same time, job satisfaction of hospital doctors tends to increase. We conclude that, in particular, the medical profession benefits from medical doctors in office.
Keywords: D72; I11; I18; O47; P16; 330; hospitals; health minister; productivity; TFP; favoritism; profession; technocracy